2013
DOI: 10.1186/1750-1326-8-35
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster as a model organism for Alzheimer’s disease

Abstract: Drosophila melanogaster provides an important resource for in vivo modifier screens of neurodegenerative diseases. To study the underlying pathogenesis of Alzheimer’s disease, fly models that address Tau or amyloid toxicity have been developed. Overexpression of human wild-type or mutant Tau causes age-dependent neurodegeneration, axonal transport defects and early death. Large-scale screens utilizing a neurodegenerative phenotype induced by eye-specific overexpression of human Tau have identified several kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
124
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(130 citation statements)
references
References 82 publications
5
124
0
1
Order By: Relevance
“…Despite this, Congo Red which blocks Aβ oligomerisation was able to rescue the shortened lifespan. Again, the data showed that intracellular Aβ and extracellular soluble Aβ cause neurodegeneration (14). This debunking of the common consensus whereby Aβ40 and Aβ42 peptides are the root behind toxicity in AD pathogenesis has also been shown in previous studies utilising other animal models (57,58).…”
Section: Drosophila's Contribution To Understanding Ad Amyloidosis Pamentioning
confidence: 60%
See 3 more Smart Citations
“…Despite this, Congo Red which blocks Aβ oligomerisation was able to rescue the shortened lifespan. Again, the data showed that intracellular Aβ and extracellular soluble Aβ cause neurodegeneration (14). This debunking of the common consensus whereby Aβ40 and Aβ42 peptides are the root behind toxicity in AD pathogenesis has also been shown in previous studies utilising other animal models (57,58).…”
Section: Drosophila's Contribution To Understanding Ad Amyloidosis Pamentioning
confidence: 60%
“…The peptide binds to other Aβ peptides and accumulate into fibrils. It should be noted that the three main genes posing risk elements for EOFAD are part of the amyloid pathology, namely APP, Presenilin 1 and Presenilin 2 (14).…”
Section: The Amyloid Pathway Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Drosophila melanogaster has been the subject of intensive genetic analyses investigating the role of genes implicated in various biological phenomena (Pandey and Nichols, 2011;Prüßing et al, 2013). Drosophila also possesses an Ogg1 ortholog, which excises 8-oxo-guanines from γ-irradiated DNA in vitro.…”
Section: Introductionmentioning
confidence: 99%